Monitoring and modeling the influence of snow pack and organic soil on a permafrost active layer, Qinghai-Tibetan Plateau of China - Zhou, J.; Kinzelbach, W.; Cheng, G. D.; Zhang, W.; He, X. B.; Ye, B. S. (Cold Regions Science and Technology, 2013)
ISSN:0165-232X ISSN:1872-7441